2017
DOI: 10.1186/s13071-017-2148-y
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma spp. in dogs and owners in north-western Morocco

Abstract: Background Anaplasma phagocytophilum is an emerging tick-borne zoonotic pathogen of increased interest worldwide which has been detected in northern Africa. Anaplasma platys is also present in this region and could possibly have a zoonotic potential. However, only one recent article reports on the human esposure to A. phagocytophilum in Morocco and no data are available on canine exposure to both bacteria. Therefore, we conducted a cross-sectional epidemiological study aiming to assess both canine and human ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
(82 reference statements)
4
13
0
Order By: Relevance
“…No statistically significant differences were found in the prevalence of Anaplasma spp. in animals or humans exposed or not to ticks [28,29]; the same results were found in the current study. According to A i t L b a c h a et al [57], and lower than that estimated in Angola (100 %) [34],…”
Section: Comparative Study Of the Two Methods (Mgg And Celisa)supporting
confidence: 91%
“…No statistically significant differences were found in the prevalence of Anaplasma spp. in animals or humans exposed or not to ticks [28,29]; the same results were found in the current study. According to A i t L b a c h a et al [57], and lower than that estimated in Angola (100 %) [34],…”
Section: Comparative Study Of the Two Methods (Mgg And Celisa)supporting
confidence: 91%
“…Previous studies have reported genetic relatedness between A. phagocytophilum infecting animals and humans [15,35]. Similarly, in this study isolates from Olive baboons appear to be genetically related to those of human (MF582329.1) (Figure 3).…”
Section: Discussionsupporting
confidence: 78%
“…This can be explained by the high variability of p44 gene, which includes intra-species variability, with consequent protein polymorphism and the generation of antigenic variations [33,34]. The 16S rRNA gene yielded positive bands and therefore reinforced that it is a good marker for detection of Anaplasma as reported by other studies [20,27,35].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This was confirmed by sequence analysis of 16S rRNA (humans, dogs and rodents) and gltA (dogs and rodents) genes. Reports of human granulocytic anaplasmosis occurring in Africa have been few [ 57 , 58 ]. In South Africa, there have been no reported A. phagocytophilum infections in humans.…”
Section: Discussionmentioning
confidence: 99%